Theoretical Computation of Electron Density in Laser-Induced Carbon Plasma using Anisimov Model - Alhamadani, Mohammed (Iraqi Journal of Physics, 2023)
In this work, electron number density was calculated using Matlab program code and the writing algorithm of the program. Electron density was calculated using the Anisimov model in a vacuum environment. The effect of spatial coordinates on the electron density was investigated in this study. It was found that the Z axis distance direction affects the electron number density (ne). There are many processes such as excitation, ionization, and recombination within the plasma that may affect the density of electrons. The results show that as Z axis distance increases electron number density decreases because of the recombination of electrons and ions at large distances from the target and the loss of thermal energy of the electrons at high distances with the progress of time and at a certain coordinate. The target is carbon (graphite). The results were selected in four dimensions where three of them belong to the spatial coordinates x, y, z and the fourth dimension is the electron density (ne).